9+3x=6-(2x)

Simple and best practice solution for 9+3x=6-(2x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9+3x=6-(2x) equation:


Simplifying
9 + 3x = 6 + -1(2x)

Remove parenthesis around (2x)
9 + 3x = 6 + -1 * 2x

Multiply -1 * 2
9 + 3x = 6 + -2x

Solving
9 + 3x = 6 + -2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2x' to each side of the equation.
9 + 3x + 2x = 6 + -2x + 2x

Combine like terms: 3x + 2x = 5x
9 + 5x = 6 + -2x + 2x

Combine like terms: -2x + 2x = 0
9 + 5x = 6 + 0
9 + 5x = 6

Add '-9' to each side of the equation.
9 + -9 + 5x = 6 + -9

Combine like terms: 9 + -9 = 0
0 + 5x = 6 + -9
5x = 6 + -9

Combine like terms: 6 + -9 = -3
5x = -3

Divide each side by '5'.
x = -0.6

Simplifying
x = -0.6

See similar equations:

| (3x-30)(3x+3)-(2x-1)(2x-1)=0 | | T=C(9+AB)forB | | 2128.88=2100.00(1+0.25) | | 5y^2+8y=13 | | cos(4x)-cos(2x)+sin(3x)=0 | | 2x-3-1= | | (3x-30)(3x+3)-(2x-1)*2=0 | | 5x-57-2x= | | X^4-3x^3+x^2-3x+3=0 | | 35/20=n/4 | | 10=-7x-x^2 | | 4x+-5=7x-3 | | -(6v-2x-1)= | | -2-3-1= | | 270=0.5x^2+36x-40 | | 5-4-4= | | (2x+3)(x-6)-(5x+3)(3x+4)= | | 9r^2-5=76 | | ×/5=7.5 | | 4y+12=7y+36 | | 5m+4=3m+16 | | x^2-2x+2y^2=8 | | 100-50/10*5 | | -23=6r+16 | | 8-6-2= | | (3x-30)(3x+3)-(2x-1)=0 | | y^2-26y+45=0 | | 8m+5=5m+15 | | 11-2x=-x-3 | | -23=6r+12 | | 18r+4= | | -23=16r-5 |

Equations solver categories